2021
DOI: 10.18632/aging.203615
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD5L is associated with cardiovascular events and all-cause mortality in individuals with chronic kidney disease

Abstract: This study assessed the association of CD5L and soluble CD36 (sCD36) with the risk of a cardiovascular event (CVE), including CV death and all-cause mortality in CKD. We evaluated the association of CD5L and sCD36 with a predefined composite CV endpoint (unstable angina, myocardial infarction, transient ischemic attack, cerebrovascular accident, congestive heart failure, arrhythmia, peripheral arterial disease [PAD] or amputation by PAD, aortic aneurysm, or death from CV causes) and all-cause mortality using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…However, in another study in which 1516 participants with chronic kidney disease were followed for 4 years, plasma concentrations of sCD36 were not associated with an increased risk of the defined or predefined composite cardiovascular end point and all‐cause mortality. 20 However, increased plasma concentrations of CD5 L could be a predictor of an increased risk of cardiovascular events in these patients. Overall, sCD36 may be a predictive or diagnostic marker for patients with MI, although further clinical studies are necessary in the future (Table 2 ).…”
Section: Association Between Each Sr and ...mentioning
confidence: 97%
See 1 more Smart Citation
“…However, in another study in which 1516 participants with chronic kidney disease were followed for 4 years, plasma concentrations of sCD36 were not associated with an increased risk of the defined or predefined composite cardiovascular end point and all‐cause mortality. 20 However, increased plasma concentrations of CD5 L could be a predictor of an increased risk of cardiovascular events in these patients. Overall, sCD36 may be a predictive or diagnostic marker for patients with MI, although further clinical studies are necessary in the future (Table 2 ).…”
Section: Association Between Each Sr and ...mentioning
confidence: 97%
“…Along with the transport of HDL, SR‐BI can promote the clearance of LDL, very LDL, and apolipoprotein A, contributing to the attenuation of atherosclerosis. 20 CD36 (a gene located on chromosome 7 of humans) is expressed on macrophages, monocytes, ECs, SMCs, platelets, and cardiac myocytes (Figure 1 ; Table 1 ) and has been reported to play an important role in inflammation, angiogenesis, and atherosclerosis by binding different ligands. 21 In macrophages, oxLDL can increase CD36 expression, and CD36 recognizes and facilitates the endocytosis of oxLDL, resulting in the development of foam cells and the progression of atherosclerosis.…”
Section: Association Between Each Sr and ...mentioning
confidence: 99%
“…Agra-Bermejo et al suggested that isoproterenol treatment of patients with HF or atrial fibrillation significantly increased CD5L secretion from epicardial adipose tissue, which may activate the toll-like receptor 4/nuclear factor-kappa B (NF-κB) signaling pathway and produce pro-inflammatory cytokines ( Agra-Bermejo et al, 2020 ). Circulating CD5L is highly correlated with the risk of cardiovascular events in patients with chronic kidney dysfunction ( Castelblanco et al, 2021 ). Moreover, CD5L promotes atherosclerosis by increasing the formation of macrophage foam cells and CD36-mediated oxidized low-density lipoprotein uptake ( Amézaga et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Musante et al [437], Han et al [438], Zhang et al [439], Sato et al [440], Yang et al [441], El-Aouni et al [442], Perisic et al [443], Chung et al [444], Wilkening et al [445], Kahvecioglu et al [446], Hu et al [447] and Worthmann et al [448] revealed that ALB (albumin), KLF15, ATF3, LPL (lipoprotein lipase), CUBN (cubilin), ILK (integrin linked kinase), PLEKHH2, TNF (tumor necrosis factor), CCR2, SPON2, LRRC55 and IGFBP1 might be the potential targets for FSGS diagnosis and treatment. Alves et al [449], Ma et al [450], Esposito et al [451], Ai et al [452], Lu et al [453], Bui et al [454], Bao et al [455], Zuo et al [456], Su et al [457], Wang et al [458], Šalamon et al [459], Harskamp et al [460], Ćwiklińska et al [461], Hishida et al [462], Gunay-Aygun et al [463], Simpson et al [464], Svenningsen et al [465], Wang et al [466], Rao et al [467], Chen et al [468], Bedin et al [469], Cao et al [470], Jang et al [471], de Frutos et al [472], Lin et al [473], Wang et al [474], Liu and Zhuang [475], Feng et al [476], Yu et al [477], Reed et al [478], Milillo et al [479], Chen et al [74], Chen et al [480], Vieira et al [76], Charlton et al [481], Shi et al [482], Zhou et al [483], Nazari et al [241], Greene et al [484], Lazar et al [485], Jobst-Schwan et al [486], Du et al [487], Liu et al [85], Liu et al [488], Liu et al [489], Lee et al [490], Wen et al [491], Sakai et al [492], Zhang et al [493], Wang et al [494], CD5L Castelblanco et al [251], Chen et al [495], Swanson et al [496], Ksiazek, [497], Li et al [498], Zhang et a...…”
Section: Discussionmentioning
confidence: 99%